Exploring the Knowledge of Family Relationships as an Educational Content for an Intercultural School Curriculum in the Mapunche Communities - Quintriqueo M., Segundo; Maheux, Gisèle (Revista de Psicología, 2004)
Since the school institution has taken place in mapunche communities, the mapunche cultural patrimony has not been formalized as a content in the educational school curriculum. An aspect these patrimony components considered important are related to the study of natural, social and cultural milieu. Through an ethnographically focused qualitative research, this article explores the absence of the indigenous cultural patrimony as formal area of knowledge in the educational content of the school curriculum, and explores this question from the point of view of the historical schooling process in the context of schools located in mapunche communities. The goal of this study is to develop a conceptual representation of family relationship knowledge and the socialization process in the context of the family and the community. A thematic content analysis of data was performed in order to describe the current state of knowledge of family relationship, and then to provide relevant knowledge to document the training content of Initial Teacher Training in Intercultural Education and the curriculum of schools located in an indigenous context, particularly the mapunche communities. The discussion of the results shows that the family and the community carry on a socialization process that allows transmitting certain mapunche educational content categories which would be worth incorporating into the individual training of school students.